Integration of science and learning process as a condition of the formation of future teachers didactic philological specialties in higher educational institutions (Pedagogy of Higher and Secondary Education, 2012)
Mishenina T. Integration of science and learning process as a condition of the formation offuture teachers didactic philological specialties in higher educational institutions.The paper theoretically substantiates efficient formation of future teachers didactic philologicalspecialties in higher educational institutions by successive integration of science and education process. The features of the organization of research work of students through the use of methods of scientific knowledge as methods of mastering academic subjects in the school search.
Keywords: teaching and learning process; research and development activities; future teachers philological specialties; higher teacher education institution